2018
DOI: 10.1371/journal.ppat.1007125
|View full text |Cite
|
Sign up to set email alerts
|

DDX3 suppresses type I interferons and favors viral replication during Arenavirus infection

Abstract: Several arenaviruses cause hemorrhagic fever (HF) diseases that are associated with high morbidity and mortality in humans. Accordingly, HF arenaviruses have been listed as top-priority emerging diseases for which countermeasures are urgently needed. Because arenavirus nucleoprotein (NP) plays critical roles in both virus multiplication and immune-evasion, we used an unbiased proteomic approach to identify NP-interacting proteins in human cells. DDX3, a DEAD-box ATP-dependent-RNA-helicase, interacted with NP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 92 publications
(130 reference statements)
0
50
0
Order By: Relevance
“…To date, lists of host-cell proteins associated with various arenavirus infections have been established, providing new bases to investigate the potential roles of such interactions during the course of infection. With the exception of one study, which focused on the proteins of cellular origin associated with the Z protein of JUNV, most reports have focused on the NP and L interactomes during JUNV and LCMV infection [44][45][46][47][48]. However, these reports were based on the expression of tagged viral proteins through transfection or infection with genetically modified viruses and the identification of associated host-cell partners after purification and mass spectrometry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, lists of host-cell proteins associated with various arenavirus infections have been established, providing new bases to investigate the potential roles of such interactions during the course of infection. With the exception of one study, which focused on the proteins of cellular origin associated with the Z protein of JUNV, most reports have focused on the NP and L interactomes during JUNV and LCMV infection [44][45][46][47][48]. However, these reports were based on the expression of tagged viral proteins through transfection or infection with genetically modified viruses and the identification of associated host-cell partners after purification and mass spectrometry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent large-scale protein interaction screen revealed that both OW and NW arenavirus NPs interact with the host DEAD-box ATP-dependent RNA helicase, DDX3 [81]. DDX3 exhibits a proviral role for arenaviruses, as replication of LCMV, LASV, and JUNV was substantially impaired in DDX3 knockout cells [81]. Two different mechanisms have been proposed for the proviral effect of DDX3.…”
Section: Molecular Mechanisms For Arenavirus Antagonism Of the Ifn Rementioning
confidence: 99%
“…Two different mechanisms have been proposed for the proviral effect of DDX3. Early in infection, DDX3 assists in viral RNA replication, as supported by the reduced arenavirus minigenome replication in DDX3 knockout cells [81]. Mutation in the DDX3 ATPase and helicase domains also leads to reduced minigenome replication, indicating that these domains are essential for the proviral function of DDX3 [81].…”
Section: Molecular Mechanisms For Arenavirus Antagonism Of the Ifn Rementioning
confidence: 99%
See 2 more Smart Citations